An Analysis of The Determinants of Unemployment Rate in West Java - Rayhan, Emir; Saputra, Putu Mahardika Adi (Journal of Development Economic and Social Studies, 2025)
Unemployment is a social and economic issue that affects economic stability and is quite seriously faced by developing countries, especially Indonesia. This is influenced by various interrelated factors, including average length of schooling, investment, minimum wage. This research aims to analyze the influence of average length of schooling, investment, minimum wage, sector industry, and COVID-19 on the unemployment rate in West Java Province for the period 2010-2022. This research uses a quantitative research approach and secondary data types. The analysis technique used to determine the factors that influence the unemployment rate uses panel data regression. The research results show that the average length of schooling has a negative and significant influence, the sector industry and COVID-19 have a positive and significant influence. Meanwhile, investment and minimum wages have no influence on the unemployment rate in West Java Province. The implications of the findings in this research are that the government needs to support industrial growth so that it can achieve a more inclusive labor market and increase cooperation with the private sector, academics and society regarding more effective and targeted policy implementation.